Molecular Hysteresis: Hydrologically Driven Changes in Riverine Dissolved Organic Matter Chemistry During a Storm Event. Issue 4 (4th April 2019) - Wagner, Sasha; Fair, Jennifer Hoyle; Matt, Serena; Hosen, Jacob D.; Raymond, Peter; Saiers, James; Shanley, James B.; Dittmar, Thorsten; Stubbins, Aron
Abstract: Hydrological events, driven by rainfall, control the amount and composition of dissolved organic matter (DOM) mobilized through river networks. In forested watersheds, the concentration, composition, and reactivity of DOM exported changes as baseflow transitions to storm flow, with major implications to downstream biogeochemistry. Hysteresis describes an observed difference between in‐stream solute concentration/signal and discharge. By studying the relationship between DOM and stream discharge, we refine our understanding of the environmental and hydrological factors that influence the quantity and quality of stream DOM. The main objective of this study was to track hysteretic changes in riverine DOM molecular composition during storm events. Samples were collected from nested sites within the Passumpsic River catchment (Vermont, USA), a tributary of the Connecticut River. High‐resolution monitoring of fluorescent DOM (via in situ sensors) and automated collection of discrete samples captured short‐term, hydrologically driven variations in DOM concentration and composition. Ultrahigh‐resolution mass spectrometry revealed an enrichment in aliphatic compounds at storm onset, while aromatic and polyphenolic compounds were more enriched at peak discharge. Molecular hysteresis patterns were similar across stream orders, indicating that fresh, terrigenous DOM is quickly shunted downstream, through the river network, during pulses of high discharge. Plain Language Summary: During storm events, rainfall‐runoff processes mobilize large amounts of dissolved organic matter from the land and through river networks. The relationship between stream discharge and dissolved organic matter quantity and composition can vary over the course of a storm event; this variation is termed hysteresis . We examined hysteresis in a forested New England watershed (Vermont, USA) to better understand the location and timing of dissolved organic matter reactivity in river systems. In‐stream sensors captured high‐frequency, storm‐driven changes in dissolved organic matter quantity. Discrete water samples were collected across the storm event for molecular analysis of dissolved organic matter. Molecular analyses revealed differences in dissolved organic matter composition between storm onset and peak discharge. Storm events shunt molecularly diverse organic material further downstream, potentially shifting reactivity hotspots from upper to lower reaches of the watershed. Key Points: Ultrahigh‐resolution mass spectrometry revealed molecular hysteresis of dissolved organic matter in a forested New England catchment Aliphatic compounds were enriched at storm onset, and aromatic compounds were enriched at peak discharge Similarities in molecular hysteresis across stream orders suggested event‐driven transport of fresh organic material further downstream